Manipulation of Autophagy and Apoptosis Facilitates Intracellular Survival of Staphylococcus aureus in Human Neutrophils - Mulcahy, Michelle E.; O’Brien, Eóin C.; O’Keeffe, Kate M.; Vozza, Emilio G.; Leddy, Neal; McLoughlin, Rachel M. (Frontiers in Immunology, 2020)
Polymorphonuclear neutrophils (PMN) are critical for first line innate host immune defence against Staphylococcus aureus. The intracellular milieu of PMN presents a seemingly inhospitable environment that would preclude intracellular survival of bacteria and the fact that mature circulating PMN maintain a short half-life, ending in constitutive apoptotic cell death, makes them even less likely candidates for manipulation by bacteria. However, there is significant evidence to suggest that S. aureus can survive intracellularly within PMN and this contributes to persistence and dissemination during infection. The precise mechanism by which S. aureus parasitizes these cells remains to be established. Herein we propose a novel mechanism by which S. aureus subverts both autophagy and apoptosis in PMN in order to maintain an intracellular survival niche during infection. Intracellular survival of S. aureus within primary human PMN was associated with an accumulation of the autophagic flux markers LC3-II and p62, while inhibition of the autophagy pathway led to a significant reduction in intracellular survival of bacteria. This intracellular survival of S. aureus was coupled with a delay in neutrophil apoptosis as well as increased expression of several anti-apoptotic factors. Importantly, blocking autophagy in infected PMN partially restored levels of apoptosis to that of uninfected PMN, suggesting a connection between the autophagic and apoptotic pathways during intracellular survival. These results provide a novel mechanism for S. aureus intracellular survival and suggest that S. aureus may be subverting crosstalk between the autophagic and apoptosis pathways in order to maintain an intracellular niche within human PMN.